KARAKTERISTIK MATERIAL BAHAN KONSTRUKSI DI BEBERAPA LOKASI DALAM KABUPATEN MUARO JAMBI - Suhendra Suhendra; Fakhrul Rozi Yamali; Tristiana Ningfuri; Fakhrul Rozi Yamali (Jurnal Ilmiah Universitas Batanghari Jambi, 2014)
This study aims to determine the potential of construction excavated material  used as  material of construction materials derived from Muaro Jambi. The study focused on the aggregates for concrete.The study was preceded by surveys of the location of the material and then sorted based on the location of geological and productivity quarry producer. Furthermore, research conducted at the Laboratory of the Faculty of Engineering, University of Batanghari to get the physical characteristics of materials in order to obtain results and comparison with the applicable specifications for the concrete material.Results are expected to help the mapping of potential construction materials excavated material C in some areas in Jambi Muaro analysis and recommendations based on the use of laboratory test resultsKey words:   pasir, kerikil, gradasi